Association between the extent of intrapulmonary spread on chest CT and false-negative results of T-SPOT.TB in pulmonary tuberculosis: a retrospective study - Ryo Sato; Naoki Takasaka; Yusuke Hosaka; Taiki Fukuda; Kyota Shinfuku; Makiko Takatsuka; Tsukasa Hasegawa; Masami Yamada; Yumie Yamanaka; Kai Ryu; Takeo Ishikawa; Jun Araya (BMC Infectious Diseases)
Abstract Background The T-SPOT.TB assay is widely used for the adjunctive diagnosis of tuberculosis (TB). However, clinicians often encounter false-negative T-SPOT.TB results. The extent of TB spread may influence host immune functions, which can influence the results of the T-SPOT.TB test. However, few previous reports have investigated the association between radiologic pulmonary tuberculosis (PTB) severity and T-SPOT.TB test results. Methods We retrospectively investigated patients with culture-confirmed pulmonary TB (PTB) at the Jikei University Daisan Hospital between September 2016 and December 2021. We aimed to clarify the association of PTB severity, according to computed tomography (CT), with the false-negative results of the T-SPOT.TB test. Results Among 193 patients with PTB, 43 (22.3%) had false-negative T-SPOT.TB results. High rates of false-negative results were noted for 7/18 (38.9%) patients with PTB spread in two lung segments (mild PTB) and 16/39 (41.0%) patients with PTB spread in 19 lung segments (severe PTB). Multivariate logistic regression analysis showed that mild or severe PTB (odds ratio [OR]: 3.23; 95% confidence interval [CI]: 1.46–7.13; P = 0.004) and lymphopenia (OR: 3.33; 95% CI: 1.20–9.26; P = 0.02) were statistically significant risk factors for false-negative results. Conclusions Mild or severe intrapulmonary lesions on chest CT might be associated with the false-negative results of the T-SPOT.TB assay. Additionally, estimating the intrapulmonary spread of PTB using chest CT could serve as a useful supplementary tool in diagnosing patients with PTB who receive false-negative results on the T-SPOT.TB test.